2016
DOI: 10.18632/oncotarget.13823
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a novel one-stop ISET device to capture CTCs and its clinical application

Abstract: IntroductionCirculating tumor cells (CTCs) play a crucial role in cancer metastasis. In this study, we introduced a novel isolation method by size of epithelial tumor cells (ISET) device with automatic isolation and staining procedure, named one-stop ISET (osISET) and validated its feasibility to capture CTCs from cancer patients. Moreover, we aim to investigate the correlation between clinicopathologic features and CTCs in colorectal cancer (CRC) in order to explore its clinical application.ResultsThe capture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 49 publications
4
58
1
Order By: Relevance
“…It has been estimated that approximately 1×106 CTCs per gram of tumour tissue are released into the circulation daily [14], but most of them are recognized and cleared by immune cells in the blood microenvironment; ultimately, less than 0.1% CTCs can reach distant organs to form metastasis lesion [15]. The above perspective has also been confirmed in our previous studies, which showed that the number of CTCs was negatively correlated with lymphocyte count in peripheral blood [16,17]. Of note, we also found that CTC count had a negative correlation with decreased prognostic nutrition index (PNI) [18], which is an important indicator reflecting the perioperative nutritional conditions of patients with malignant gastrointestinal tract tumours [19].…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…It has been estimated that approximately 1×106 CTCs per gram of tumour tissue are released into the circulation daily [14], but most of them are recognized and cleared by immune cells in the blood microenvironment; ultimately, less than 0.1% CTCs can reach distant organs to form metastasis lesion [15]. The above perspective has also been confirmed in our previous studies, which showed that the number of CTCs was negatively correlated with lymphocyte count in peripheral blood [16,17]. Of note, we also found that CTC count had a negative correlation with decreased prognostic nutrition index (PNI) [18], which is an important indicator reflecting the perioperative nutritional conditions of patients with malignant gastrointestinal tract tumours [19].…”
Section: Introductionsupporting
confidence: 58%
“…CTC isolation was performed using the CTCBIOPSY® device (Wuhan YZY Medical Science and Technology Co., Ltd., Wuhan, China), as described in our previous studies [11,16]. The specific implementation was completed by the professional staff of Wuhan YZY Medical Science and Technology Company according to the manufacturer's instruction.…”
Section: Ctc Isolation and Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy achieved a diagnostic sensitivity of 83.05% and a specificity of 100%, when using a cut-off value of 2 CTCs/3.2 ml of peripheral blood. The detection rate of CTCs with this method was higher than that of the CellSearch ® system, which has been reported to be 15.33% (10), higher than that of the ISET ® method, which has been reported to be 35% (20), and higher than that of the approach using RT-qPCR and ECT2, which has been reported to be 59% (21). Furthermore, the Cyttel method requires less peripheral blood (3.2 ml) than the CellSearch ® system (7 ml).…”
Section: Discussionmentioning
confidence: 59%
“…The methods for CTC detection have been recently improved. Chen et al (20) introduced a novel isolation method, known as the ISET ® system, involving automatic isolation and staining procedures to capture CTCs, and revealed that CTCs were detected in 38/72 (52.8%) patients with CRC. In another study based on nested RT-qPCR, epithelial cell transforming 2 (ECT2) was screened as a candidate marker gene for quantifying CTCs, with a detection rate of ECT2 of ~60% in patients with different stages of CRC (21).…”
Section: Discussionmentioning
confidence: 99%